The management on fire protection system in hotel at Shah Alam / Nurul Hazirah Azhari - Azhari, Nurul Hazirah (Faculty of Architecture, Planning and Surveying, 2014)
Quite often if not always, it is the occupants for no mistake of their own who fall victim to fire. Besides damage to their belongings and property, some occupants are burned to death for not knowing what to do in the event of fire. Even though hotel are provided with the most sophisticated fire protection features, assurance of safety to building occupants is questionable and held in doubt. Fire outbreaks occur as a result of “human factors”, such as carelessness, negligence or simply a lack of fire protection awareness. In response to this, fire protection management has become an integral aspect in the daily operations of hotel buildings. This study presents the results of the investigation on fire protection management in hotel buildings. The objectives of the study are to identify the type of fire protection system provided in hotel; to highlight the causes of fire occurred at hotel; and to determine the problem in managing fire protection system. The methodology for conducting the study involved literature review, data collection and analysis of results using the Average Index Method. The process of data collection involved obtaining primary data from the respondents by conducting questionnaire surveys at the selected building case studies. From this study, it is determined that the three hotel of fire protection system are the education and training of hotel building users in fire protection; the implementation of fire and evacuation drill procedures; and to provide clear signage indicating exit routes and location of fire safety equipment. The three best methods to improve fire protection of hotel building users are to ensure that flammable materials are stored in a safe area; to conduct more educational and training programs for users; and to ensure that there are clear or “glow in the dark” signage indicating exit routes and location of fire safety equipment. It is hoped that this study will provide some useful insight on the important aspects of fire protection management and thus, help guide hotel building users to safeguard both their life and property.